The human embryo following biopsy on day 5 versus day 3: viability, ultrastructure and spindle/chromosome configurations. Issue 2 (August 2022) - Chatzimeletiou, Katerina; Petrogiannis, Nikos; Sioga, Antonia; Emmanouil-Nikoloussi, Elpida-Niki; Panagiotidis, Yannis; Prapa, Marialena; Patrikiou, Antonios; Filippa, Maria; Zervakakou, Glykeria; Papanikolaou, Kyriakos; Makedos, Anastasios; Kolibianakis, Efstratios; et al.
Abstract: Research question: Are there any differences in viability, spindle abnormalities and mitochondrial and other organelle structures amongst embryos biopsied on day 3 versus day 5 before and after vitrification? Design: A total of 240 day 3 biopsied embryos that developed to blastocysts but were rejected for transfer following preimplantation genetic testing for monogenic/single gene defects (PGT-M) ( n  = 115) or for aneuploidies (PGT-A) ( n  = 125) were divided into two groups: (i) 120 blastocysts treated for viability, spindle/chromosome configuration (SCC) analysis and transmission electron microscopy (TEM) analysis (fresh n  = 20, n  = 20, n  = 20 and following vitrification/warming n  = 20, n  = 20, n  = 20); (ii) 120 embryos were re-biopsied at the blastocyst stage and treated for viability, SCC and TEM analysis (fresh n  = 20, n  = 20, n  = 20 and following vitrification/warming n  = 20, n  = 20, n  = 20). Also, 60 vitrified blastocysts biopsied only on day 5 that were rejected for transfer following PGT-M ( n  = 6) or PGT-A ( n  = 54) were treated following warming for viability ( n  = 20), SCC ( n  = 20) and TEM analysis ( n  = 20). Results: No differences were observed in SCC and ultrastructure between embryos biopsied on day 5 and day 3 but following vitrification higher numbers of abnormal spindles, distension of mitochondria, multivesicular bodies, lipofuscin droplets, altered cell junctions and occasionally excessive accumulation of glycogen granules were evident. The fresh day 3 biopsied group also had a lower incidence of damaged (propidium iodide-stained) cells compared with the fresh day 3+5 ( P  = 0.02) and the vitrified day 5 ( P  = 0.001) biopsied groups. Conclusions: Biopsies on day 5 and day 3 do not adversely affect embryo viability, SCC or ultrastructure, although following vitrification minimal embryo quality-dependent increases in spindle abnormalities and cell damage are observed.